1979
DOI: 10.1111/j.1365-2427.1979.tb01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometric measurement of alkaline phosphatase activity in algae

Abstract: SUMMARY. Using both cultures of algae and natural populations, alkaline phosphatase activity located on the cell surface has been measured by a fluorometric procedure. This was done in order to establish optimum standard conditions for the measurement of this activity as an indicator of phosphorus deficiency and to provide a means of interpreting alkaline phosphatase measurements on natural phytoplankton populations. A concentration of 10 μM o‐methylfluorescein phosphate saturates or nearly saturates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
2
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 34 publications
5
69
2
1
Order By: Relevance
“…In contrast to urease, APA is a well-studied enzyme that is known to be inducible upon limitation by DIP and is often indicative of P-limitation (Healey & Hendzel 1979, Chrost 1991, Cotner & Wetzel 1991. Higher rates of APA have previously been observed in the south-central region of Florida Bay compared to the northwest and north-central regions (Cotner et al 2000), and the long-term median rates (volumetric basis) of APA have been shown to be higher in the central region than in the eastern and western basin .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to urease, APA is a well-studied enzyme that is known to be inducible upon limitation by DIP and is often indicative of P-limitation (Healey & Hendzel 1979, Chrost 1991, Cotner & Wetzel 1991. Higher rates of APA have previously been observed in the south-central region of Florida Bay compared to the northwest and north-central regions (Cotner et al 2000), and the long-term median rates (volumetric basis) of APA have been shown to be higher in the central region than in the eastern and western basin .…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al (2003) found that urease content per cell was significantly higher for the dinoflagellate P. minimum than for the either the diatom Thalassiosira weissflogii or the pelagophyte Aureococcus anophagefferens; however, on a per cell volume basis, A. anophagefferens had the highest activity. In this study the easternmost bay site (Stn 7) was characterized by the highest rate of biomass-normalized urease activity and was composed of a higher relative proportion of peridinin-containing dinoflagellates, which would be consistent with the above relationships.In contrast to urease, APA is a well-studied enzyme that is known to be inducible upon limitation by DIP and is often indicative of P-limitation (Healey & Hendzel 1979, Chrost 1991, Cotner & Wetzel 1991. Higher rates of APA have previously been observed in the south-central region of Florida Bay compared to the northwest and north-central regions (Cotner et al 2000), and the long-term median rates (volumetric basis) of APA have been shown to be higher in the central region than in the eastern and western basin .…”
mentioning
confidence: 99%
“…Acid phosphatases presumably function similarly to alkaline phosphatases in that they are phosphomonoesterase enzymes that help supply algae with inorganic P (Healey and Hendzel, 1979). Phosphatase activity commonly increases in the presence of low inorganic P concentrations; therefore, high biomass-specific phosphatase activity indicates P-limitation in algal populations (Healey, 1973;Healey and Hendzel, 1979;Wetzel, 1983). However, the effects of Al on acid phosphatase activity are poorly understood and contradictory.…”
Section: Direct Effects Of Aluminum On Phosphorus Physiologymentioning
confidence: 99%
“…Many phytoplankton species evolved different strategies to ameliorate the toxic effects of As 5+ , including reduction to arsenite (As 3+ ) and methylation to monomethyl-(MMAs) and dimethylarsenic (DMAs). These detoxification products are less harmful and easier to excrete (Andreae and Klumpp 1979;Sanders and Riedel 1993;Hellweger et al 2003). Hellweger et al (2003) proposed a mechanistic model with a limited methylation capacity due to slower kinetics compared with the preceding reduction.…”
Section: Introductionmentioning
confidence: 99%
“…These detoxification products are less harmful and easier to excrete (Andreae and Klumpp 1979;Sanders and Riedel 1993;Hellweger et al 2003). Hellweger et al (2003) proposed a mechanistic model with a limited methylation capacity due to slower kinetics compared with the preceding reduction. Such capacity may be exceeded during luxury P uptake because the chances of taking up As 5+ increase with higher rates of P uptake.…”
mentioning
confidence: 99%